Environmental Legal Responsibility Of Non-Metal And Rock Mining Business Persons In Sharia Perspective: Study In The City Of Tidore Islands - Rusdin Alauddin; Irham Rosidi; Abdul Aziz DP; Irawan Sangaji (Law Doctoral Program Universitas Muhammadiyah Surakarta, 2021)
Mining of non-metallic minerals and rocks is a natural resource from Allah SWT to be used properly and correctly for all of His creatures. In the City of Tidore, Islands, the use of these natural resources is illegal and does not have a mining permit. The consequences of mining activities include the physical impact of the environment being damaged such as land damage and forest damage, reduced water discharge on the ground surface, damage to public health, damage to public facilities found on roads, as well as causing community conflicts. The form of responsibility is carried out by limiting utilization activities, carrying out environmental restoration, as well as cooperation between the government and the community in supervising utilization actions that cause losses. Responsibility is not only on the government but public awareness is very important in environmental conservation efforts. In the Qur'an Surah al-Rum verse 41, it has been stated that